Assessment of current developments and future prospects of wind energy in Canada. (March 2022) - Dehghani-Sanij, A.R.; Al-Haq, A.; Bastian, J.; Luehr, G.; Nathwani, J.; Dusseault, M.B.; Leonenko, Y.
Highlights: Assessment of wind energy potential in Canada as a case study. Statistical evaluation of the status of Canada's wind power in terms of installed capacity, generation, capacity factor, and levelized cost of energy. Feasibility analysis of the potential development of wind energy in Canada's provinces and territories. Practical solutions to use wind energy, either alone or integrated with other energy sources. Abstract: The negative consequences of global warming and climate change demonstrate that conversion to carbon-free or low-carbon, sustainable, and eco-friendly energy sources is essential. Wind energy substitution, as a renewable and widely available energy source, can be an appropriate, effective, and practical contribution to reducing fossil fuel use worldwide. To show the importance of wind energy in the future global energy supply, the current status and future prospects of wind power in Canada are statistically analyzed, as a case study, in terms of installed capacity, generation, capacity factor, and insights are provided on the levelized cost of energy (LCOE). The originality of this study is to present a comprehensive basis for assessing future growth and the potential development of wind power in Canada's electricity supply mix to the year 2040 by using different predictive methods, including historical compound annual growth rate (CAGR), linear forecasting, and CAGR of 5, 10 and 15%, selected based on a presumed policy interjection at the provincial- or territorial-level. The comparative assessment of wind energy generated by various predictive methods up to 2040 shows that the historical CAGR and the CAGR of 15% respectively have the lowest and highest growth rates in meeting the total annual end-use electricity demand for Canadian provinces and territories, except for Alberta, Saskatchewan, Yukon, and Nunavut, where the lowest growth rate belongs to the linear forecasting approach. However, these predictive scenarios strongly depend on the energy policies of the provincial or territorial governments. In addition, the influence of increasing installed wind power capacity in Canada on the LCOE is examined using a linear forecasting model with various decline rates for costs. The results indicate that the reduction in LCOE robustly depends on a higher installed wind power capacity. Moreover, the relationship between the wind power capacity factor and LCOE is evaluated based on different forecasting scenarios, where it is observed that the LCOE is strongly inversely associated with capacity factor. As a general result, many regions of Canada are identified as having a highly promising wind energy potential, especially in the Gulf of St. Lawrence, either as a stand-alone source or integrated with other energy sources, along with energy storage capabilities, to meet future electricity requirements with a low carbon footprint.